Research Planning, Statistical Analysis, Ethics, and Successful Publishing - Balakumar, Pitchai; Sellappan, Renukha; Nagarkar, Shubhada; Hazra, Avijit; Jagadeesh, Gowraganahalli (Indian Journal of Pharmaceutical Education and Research, 2024)
Novice researchers are frequently inexperienced with basic concepts of research and successful scientific publishing. To strengthen their fundamental knowledge of scientific research, we recently conducted a brainstorming symposium at the 73rd Indian Pharmaceutical Congress held in Hyderabad, India in July 2024. This report highlights the symposium's key components as well as the benefits that attendees experienced. The symposium was intended to equip faculty and postgraduate and doctorate students with the skills they need to succeed in scientific research and publishing. It sought to dispel the mystery around the research process, from conception to publication, highlighting the significance of a well-conceived, reliable, reproducible, and ethically sound experimental design. Participants acquired knowledge about developing research questions and hypotheses, crafting thorough research protocols, and using statistical techniques to increase the acceptability of their findings. Our team clarified the subtleties of data interpretation, making sure that participants advanced their research aptitude. The symposium also emphasized the significance of good communication for scientists, providing delegates with guidance on how to craft papers that concisely and compellingly convey their findings, thereby increasing the likelihood of their submissions being accepted by high-impact indexed journals. The presentations also covered the ethical aspects of academic publication, emphasizing the perils of predatory journals that jeopardize the credibility of scientific communication. This symposium was not only an educational event but also a crucial step in nurturing a new generation of scientists equipped with advanced research skills and driving innovation ethically and responsibly.
Keywords: Research methodology; Scientific writing; Statistics; Journal submission; Peer review; Scientific integrity